Emotions of children with special needs and its social meaning. - Abd Rahim, Normaliza; Mansor, Noraien (Universiti Malaysia Terengganu (UMT), 2010)
The word emotion refers to a broad repertoire of perceptions, expressions of feelings and bodily changes. Emotion is a feeling that is private and subjective, a state of psychological arousal, an expression or display of distinctive somatic and autonomic responses and actions commonly "deemed", such as defending or attacking in response to a threat. This paper focuses on selected social stories to be told to a group of children with Asperger's syndrome in Malaysia. Social stories are a tool for teaching social skills to children with autism, Asperger's syndrome and related disabilities. The selected social stories would be based on Malaysian culture and the children's emotions and conversation were videotaped and analysed for its social meaning by using the content analysis approach. There are six basic emotions grouped in three pairs of opposites; joy and sadness, acceptance and disgust and anger and fear. Four subjects with aspergers's syndrome from a school in Malaysia were chosen for the purpose of this study. Three social stories were read to them repeatedly for two a day for three weeks. Subsequently, the children were able to use the social stories in their everyday lives.